A Case Control Study on Factors Influencing Suicide Attempts - Gutti, Sushmitha; Koppisetty, Surya Sunanda; Paladugu, Sruthi; Kumar Reddy, Maddirevula Maneesh; Krishna, Nalluri Murali; Rao, Nadendla Rama (Indian Journal of Pharmacy Practice)
Aim: We aim to study psychosocial, socio-demographic and personality related factors associated with suicide attempts. Methods: From 1st September 2018 to 28th February 2019, we conducted a hospital-based case control study in Department of Psychiatry, Government General Hospital, Guntur, India. One hundred forty-five cases and one hundred forty five age and sex matched controls were selected for study. Eysenck Personality Questionnaire, Modified kuppuswamy scale, Presumptive Stressful Life Event Scale, Suicide Intent Scale were used. Statistical analysis was done using computerized software. Results: Majority (n=69, 47.58%) of the suicide attempters were between 21-30 years of age. The number of suicide attempters are more in rural areas than in urban areas and it is statistically significant with an Odds Ratio 2.39. The risk of suicide attempts is more in people who are uneducated (OR – 1.51). It was observed that being an alcoholic will increases the risk of suicide attempt (OR- 1.73). The average of PSLES score of individuals is more in case group (166.8) than control group (111.386). Having a family history of suicide attempts will increases the risk of suicide attempt (OR -2.28). Conclusion: Residing in rural areas, alcoholism, having no support from family members and having more stress full life events emerged as predominant risk factors for attempting suicide.
Keywords: Suicide attempt; Socio-demographic factors; Personality traits; Stressful life events; Suicide intent; Psychiatric illnesses.